2020
DOI: 10.1002/elan.202060370
|View full text |Cite
|
Sign up to set email alerts
|

Ce0.8Sr0.2CoxFe1‐xO3‐δ (x=0.2, 0.5, 0.8) – A Perovskite‐type Nanocomposite for Application in the Oxygen Evolution Reaction in Alkaline Media

Abstract: Three perovskite-type nanocomposites, i. e. Ce 0.8 Sr 0.2 Co x Fe 1-x O 3-δ (x = 0.2, CSCF1; 0.5, CSCF2; 0.8, CSCF3), were synthesized employing the sol-gel technique, subsequent to which they were physically and electrochemically evaluated for their electrocatalytic activity towards the oxygen evolution reaction (OER) in alkaline medium (0.1 M KOH) at room temperature (25°C). Electrochemical characterisation revealed Ce 0.8 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ (CSCF3) to be the most active having the lowest overpotenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The deconvoluted cobalt 2p spectrum is displayed in Figure 4b. The two peaks at 780.3 and 796.1 eV are caused by 2p 3/2 and 2p 1/2 of Co 3+ [39], while those at 781.4 and 797.5 eV corresponds to 2p 3/2 and 2p 1/2 of Co 2+ , confirming the coexistence of Co 3+ and Co 2+ in CoNi LDH‐ Ni 3 S 2 /NF [40]. Compared to CoNi LDH/NF (Figure S4), the binding energy of CoNi LDH‐Ni 3 S 2 /NF peaks shifts to higher energies, indicating that the electron density of the Co center decreases after the formation of the heterostructure.…”
Section: Resultsmentioning
confidence: 96%
“…The deconvoluted cobalt 2p spectrum is displayed in Figure 4b. The two peaks at 780.3 and 796.1 eV are caused by 2p 3/2 and 2p 1/2 of Co 3+ [39], while those at 781.4 and 797.5 eV corresponds to 2p 3/2 and 2p 1/2 of Co 2+ , confirming the coexistence of Co 3+ and Co 2+ in CoNi LDH‐ Ni 3 S 2 /NF [40]. Compared to CoNi LDH/NF (Figure S4), the binding energy of CoNi LDH‐Ni 3 S 2 /NF peaks shifts to higher energies, indicating that the electron density of the Co center decreases after the formation of the heterostructure.…”
Section: Resultsmentioning
confidence: 96%
“…Then, by plotting the double layer current versus the scan rate, one can calculate C dl by determining the slope and thus the ECSA area [49] . C dl can also be calculated using electrochemical impedance spectroscopy as reported by Njoku and co‐authors [50] . Although, it is one of the best methods to calculate the ECSA, still, the variation in the value of the specific capacitance as determined by directly using a popular value from the publications create limitations in this method.…”
Section: Protocols For Experimental Measurements and Parameters Influ...mentioning
confidence: 99%
“…[49] C dl can also be calculated using electrochemical impedance spectroscopy as reported by Njoku and coauthors. [50] Although, it is one of the best methods to calculate the ECSA, still, the variation in the value of the specific capacitance as determined by directly using a popular value from the publications create limitations in this method. It is suggested that one should be careful while using the value of the specific capacitance as it is not necessary that the determination of surface area using the electrochemical method is the real ECSA because it does not involve interactions between reaction intermediates and electrocatalytic sites.…”
Section: Electrochemical Active Surface Area (Ecsa)mentioning
confidence: 99%